Mutual fund flows: an analysis of the main macroeconomic factors - Roquete, Raphael Moses; Figueiredo, Otavio Henrique dos Santos; Wanke, Peter Fernandes (Revista Gestão da Produção Operações e Sistemas, 2015)
This paper analyzes whether some macroeconomic factors (country risk, IBrX volatility and Interbank Certificate of Deposit) are related to mutual fund flows for the period between January 2005 and August 2014. In order to investigate whether the flow series behaved differently during this period, the Chow test was conducted for September 2008 (the month in which the Lehman Brothers investment bank collapsed). The regressions were performed and the parameters were estimated through the OLS method for both periods, the first running from January 2005 to August 2008 and the second from September 2008 to August 2014. For the period between January 2005 and August 2008, all the variables, except for the Interbank Certificate of Deposit, proved significant, at a significance level of 10%. For the subsequent period, none of the variables proved significant and the R² was very low, which may merely indicate that investors failed to analyze the main macroeconomic variables for mutual fund allocations or redemptions and simply considered other aspects, such as manager performance. Keywords: Investment Funds. Flow. Macroeconomic Factors.